Latino high school graduation defying the odds - Romo, Harriett D.; Falbo, Toni (The Hogg Foundation monograph series, 1996)
Romo and Falbo followed the school progress of 100 at-risk students in Austin, Texas, beginning in 1989 when the students were fifteen years old. Drawing on extensive interviews with the students and their parents, school records, and fieldwork in the students' schools and communities, the authors identify both the obstacles that cause many students to drop out and the successful strategies that other students and their parents pursue to ensure high school graduation. Detailed case studies allow students and parents to describe their experiences with the public schools in their own words